Financial Econometrics for Researchers in Finance and Accounting (Book). - Sunder, Shyam; Meyer, Philip E. (The Accounting Review, 1983)
Reviews the book "Financial Econometrics for Researchers in Finance and Accounting," by H. Russell Fogler and Sumdaram Ganapathy.